PENENTUAN STASIUN KERJA YANG OPTIMAL MENGGUNAKAN METODE WORKLOAD ANALYSIS DAN LINE OF BALANCING PADA PT. MEDARI KARYA MULIA - Mega Inayati Rif’ah; Nia Maulidya Dinastuty (IST AKPRIND Yogyakarta, 2018)
Medari Karya Mulia is a company working under PT. PERTAMINA.PT. Medari Karya Mulia has field in repairing service (retest, repair, dan repaint) for 3 Kg LPG tube. Aiming in making production process run efficiently, it needs a planning for grouping production activities in a several work stations. These work stations will be useful for saving needed resource (especially for human resource), and optimizing workload that can be handled by an operator. For the purpose, first, workload analysis is held on this study, so the number of operator for each production activity can be determined. Further more, duration time for each work station should be nearly same, so production flow between work stations can be smooth, and bottleneck between work stations and idle work station can be minimized. Then Rank Position Weight (RPW) method from Line of Balancing concept is done on this work for grouping production activities into several work stations, with considering result of workload analysis. Workload analysis results are 1) 53% of operator workload is less optimal (the value is < 1), and 2) there are differences between the existing number of operator for each work activity and the proposed one. RPW method result shows there are 5 work stations can be made.